Cyber Place Management and Crime Prevention: The Effectiveness of Cybersecurity Awareness Training Against Phishing Attacks - Back, Sinchul (Journal of contemporary criminal justice, 2021)
Criminologists and crime prevention practitioners recognize the importance of geographical places to crime activities and the role that place managers might play in effectively preventing crime. Indeed, over the past several decades, a large body of work has highlighted the tendency for crime to concentrate across an assortment of geographic areas, where place management tends to be absent or weak. Nevertheless, there has been a paucity of research evaluating place management strategies and cybercrime within the virtual domain. The purpose of this study was to investigate the effectiveness of place management techniques on reducing cybercrime incidents in an online setting. Using data derived from the information technology division of a large urban research university in the United States, this study evaluated the impact of an anti-phishing training program delivered to employees that sought to increase awareness and understanding of methods to better protect their “virtual places” from cybercrimes. Findings are discussed within the context of the broader crime and place literature.